(untitled) (Eurasian Research Bulletin, 2025)
This article describes the improvement of the administration based on bringing services to business entities to a new level, further increasing the tax administration literacy of the population, supporting entrepreneurship, creating an equal competitive environment and guaranteeing the rights of consumers, and encouraging the active participation of the general public in curbing the underground economy. In recent years, countries around the world have been paying special attention to the implementation of various mechanisms to prevent and reduce tax evasion by taxpayers when developing their shortterm and long-term budget-tax policy strategies. At the same time, conducting scientific research aimed at reducing illegal financial flows, analyzing the factors that cause tax evasion by taxpayers, reducing the hidden economy, and focusing on the scientific and theoretical aspects of tax evasion processes remains one of the priorities. At the same time, the fields were studied, foreign experience, scientific-practical conclusions and proposals were formed on its application in our country.